Supplementary file 1 Occurrences of species left in open nomenclature - Claybourn, Thomas; Jacquet, Sarah; Skovsted, Christian; Topper, Timothy; Holmer, Lars; Brock, Glenn (Dryad Digital Repository, 2018)
This files lists published material included in the taxa Davidonia corrugata, Xianfengella yatesi, Pelagiella subangulata and Anabarella australis. These have been included here for convenience as they are referred to in the main text, but not typically included in systematics sections for specimens with only tentative affinities for previously described species.